A Framework for the Assessment of Fiscal Consequences of Global Trade Wars - Bilousova, O. S. (Statistics of Ukraine, 2022)
The article is devoted to topical issues of assessing the consequences of trade wars for the fiscal space of third countries. The main preconditions and causes of the trade conflict between the United States and China were studied. The main models for assessing the consequences of global trade wars were analyzed. Particular attention is paid to the global integrated monetary, fiscal and global trade models, which are based on the principles of general economic equilibrium and are widely used to assess the economic consequences of global challenges, including trade wars. It was found that the global integrated monetary and fiscal model, other macroeconomic models were aimed at determining the economic consequences and effects and cannot be directly used to assess fiscal risks and likely budget losses due to global trade wars. The aim of the article is to deepen the principles of assessing the fiscal consequences of trade wars in the conditions of uncertainty in foreign economic policy and directions of restructuring of the world value chains. The economic consequences of the conflict and the channels of their spread to third countries were identified taking into account the deepening globalization processes. The direct and indirect dependence of exports and imports, GDP, investments, factor productivity level and tax revenues on changes in foreign trade, tariff increases, increasing uncertainty in world trade in the short, medium and long term is highlighted. The estimates obtained by different models are summarized. The fiscal consequences of the trade conflict between the United States and China for Ukraine as a country with a small, open and predominantly commodity economy were quantified. The inclusion in fiscal risks of probable losses of foreign trade from global trade wars, arising due to various reasons, which may decrease the tax revenues or increase the expenditures on the public support of enterprises, is justified. Changes in the methodology for assessment of fiscal risks are proposed, enabling to estimate the cost impact of fiscal risks on the public budget of Ukraine. Proposals for improvements in the statistical monitoring of business activity of enterprises, to form an appropriate information base for monitoring foreign economic activities, assessing fiscal risks and making decisions to ensure the sustainability of public finance and public support for enterprises in the conditions of global trade wars, are substantiated.